A new complex envelope behavioral model for load mismatched power amplifiers. Issue 6 (2nd February 2017) - Cai, Jialin; Gonçalves, Ricardo; Pedro, José C.
Abstract: A new dual‐input wideband dynamic Quadratic Poly‐Harmonic Distortion (D‐QPHD) model for unmatched power amplifiers (PAs) is proposed and validated in this article. Compared with the dynamic PHD (D‐PHD) model, the new approach significantly improves the prediction accuracy. As the new model has reduced complexity, it is also more robust against possible rank deficiency problems, but still preserves accuracy, when compared with the recently proposed double‐input double‐output (DIDO) model. The parameters of the new model also have smaller magnitude distribution range compared with the DIDO model, which also improves the model robustness. Hence, it provides a good modeling choice for complex envelope DIDO modeling.